Cost analysis of the first wave of the COVID-19 pandemic on human resource management in a Portuguese hospital - Santos, Eduardo; Ferreira, Ricardo J. O.; Marques, Andréa Ascensão; Sousa, Liliana; Marques, António (Journal of Nursing Referência, 2021)
Background: The COVID-19 pandemic has brought healthcare systems to the brink of collapse worldwide, imposing relevant economic challenges. Objective: To analyze the costs related to the impact of the first wave of the COVID-19 pandemic on human resource management in a Portuguese hospital. Methodology: Economic, retrospective, and single-center study. This study analyzed the costs of absenteeism, hiring new staff, and overtime work by health professionals (nurses, physicians, operational assistants, and diagnostic and therapeutic technicians) and compared data from March 1 to May 31, 2020 to the same period in 2019 to determine differences in costs. Results: Data from 6,994 health professionals were included. Compared to 2019, an additional 8,817,199.84€ were spent on staff in this trimester (absenteeism: €6,842,284.64; hiring new staff: €363,540.03; overtime work: €1,611,375.17). Conclusion: In the first trimester of the COVID-19 pandemic, the overall costs with health professionals almost tripled, representing almost €9 million more than in the same period in 2019.